Efeitos da dieta enriquecida com frutos das palmeiras Euterpe oleracea Mart. e Mauritia flexuosa L.f. na inflamação intestinal em ratos - Curimbaba, Tainan Freitas Salmeron [UNESP] (2014)
Whereas conventional treatments of inflammatory bowel disease does not represent a cure or remission of symptoms and produce severe side effects, the search for additional strategies to prevent and treat this disease is presented as a promising prospect. Based on this information, the present study aimed to evaluate the intestinal anti-inflammatory activity of the diets enriched with the fruits of açaí (Euterpe oleracea Mart.) and buriti (Mauritia flexuosa L.f.) in the acute phase of experimental model of induced inflammatory bowel disease TNBS (trinitrobenzenosulfonic acid) in rats. Due to popular uses and known nutritional values, these two palm trees in the Amazon region have great potential to act as prebiotics, antioxidants and / or modulators of the immune response. The animals were submitted to a diet containing the pulp of the fruits in the feed in a ratio of 10% for 35 days. After 48 hours of induction of the inflammatory process, the animals were sacrificed and their colons removed for the achievement of macroscopic studies (score, lesion length, weight ratio length of the colon and occurrence of diarrhea and grip), histological (light microscopy) and biochemical (total glutathione content and activity of myeloperoxidase and alkaline phosphatase enzymes). At the same time a behavioral analysis was performed using experimental models of anxiety and general activity in animals which were fed. The biochemical evaluations showed that both diets were able to avoid the depletion of glutathione levels and decrease the activity of the alkaline phosphatase and myeloperoxidase enzymes. These protective effects were accompanied by tissue recovery as observed by microscopic analysis. These results suggest that dietary supplementation with the fruits of E. oleracea Mart. (açaí) and M. flexuosa L. F. (buriti) in a proportion of 10% in the diet was responsible for the improvement of colonic inflammation induced by TNBS in rats, in this ...